The Learning Experiences of Nursing Students in Surgical Clinics Reflected in Reflection Reports - Yaprak Sarıgöl Ordin; Özlem Bilik; Hale Turhan Damar; Buket Çelik (Anı Publishing, 2018)
This research was conducted to reveal the second year nursing students learning experiences obtained from the reflection reports in surgical clinic practice.The participant of the study consisted of retrospective reports of 56 students selected by simple randomization among second year students (n=606) practicing in surgical clinics. In this study, the learning experiences that nursing students reflect on the retrospective reports in surgical clinical practice are described in five main themes and three sub-themes. Main and subthemes; Professional Development of Students (subthemes: anxiety, communication with patients and their relatives, complex patient care), Peer Education, Difficulty of Communicating with the Instructor and Action Plan. In this study, it was determined that students had anxiety during clinical practices in surgical clinics, communication problems with patients and their relatives, and some students had problems in interactions with intern students. As the students comprehend the maintenance process, it was determined that their professional development increased and motivated positive communication with the team at the clinic. It was determined that very few students were planning an action plan in their report.